Dam deformation measurements with GPS - Taşçi, Levent (My University, 2008)
The results of deformation measurements are related to direct safety of engineering structures and human life. To avoid a wrong interpretation of displacements, an appropriate deformation monitoring network must be established and the data obtained from deformation monitoring network must be carefully evaluated. Deformation measurements and analysis require the use of very accurate surveying equipment and analysis methods. The Global Positioning System (GPS) meets the requirements stated above and therefore GPS receivers were used for this research. The purpose of this work was to monitor and analyze the deformation at the crest of the Alt?nkaya dam caused by the water load at different water levels combined with the dam's weight. The secondary goal was to determine whether GPS measurements could meet the accuracy requirements for dam deformation measurements. As working area the Alt?nkaya dam is selected it is rockfill. In order to monitor and examine the deformation, a monitoring network consisting of 6 reference points and 11 object points was established. Measurements were made 4 times over 2 years using dual frequency GPS receivers with static methods. The measurements were performed and point coordinates have been determined. Then differences were calculated between periods and analyzed by iterative weighted transformation and Least Absolute Sum methods to determine the points stability.
Keywords: Dam; Deformation analysis; Deformation measurements; Global positioning system